Catalytic ozonation process using PAC/γ-Fe2O3 to Alizarin Red S degradation from aqueous solutions: a batch study. Issue 7 (3rd July 2019) - Kamarehie, Bahram; Jafari, Ali; Ghaderpoori, Mansour; Amin Karami, Mohammad; Mousavi, Khadijeh; Ghaderpoury, Afshin
Abstract: In the catalytic ozonation process used in this study, adsorption and chemical reactions were performed at the catalyst surface. This process can increase the efficiency of plain ozonation. The main aim of this study was to investigate the efficiency of the catalytic ozonation process in removing Alizarin Red S dye from colored water by Fe2 O3 coated on PAC. In this work, activated carbon powder/γ-Fe2 O3 nano-composite was modified. The BET results showed that the surface area in PAC and PAC-γ-Fe2 O3 nano-composite was 654 and 450 m 2 g −1, respectively. In this study, the best pH for removal of ARS was found to be 9. At a higher pH, the efficiency of the process decreased gradually. According to studies, catalysts increase surface area and active sites for more ozone degradation. Also, the characterization of the catalyst will play a very important role in the COP. Also, the maximum removal efficiency was observed in catalyst dose 1.1 g l −1 . The study results showed that the highest mineralization rate in ARS degradation was related to O3 /PAC/γ-Fe2 O3 . The amount of mineralization in the SOP, O3 -PAC, and O3 /PAC/γ-Fe2 O3 was 13, 25, and 40%, respectively. The finding of mineralization of ARS using the SOP reflected the low power of the ozonation process for the mineralization of pollutants.